Implementing Electronic Invoicing in Europe - Parkkonen, Neea (My University, 2022)
Organisations need to engage in continuous development to remain competitive. With digitalisation, companies are transforming business operations in a more technological direction and looking for more effective ways of doing business. Electronic invoicing is a way of adding effectiveness to invoicing processes. Electronic invoicing has been around for decades, but it has not reached the expected popularity as an invoicing method. The purpose of this research is to evaluate factors that affect the implementation of electronic invoicing in organisations in Europe, and to find out what role change management has in the process. This research was conducted as an assignment for company X. The company is in the process of developing and implementing a new information system for payment and invoicing needs that aims to improve digitalisation and advance automation. Information about the possibilities and limitations regarding the implementation of electronic invoicing across Europe is needed for the development of the information system. The research was conducted as a qualitative multiple-case study. Individuals from the assigning company and its subsidiaries were interviewed in semi-structured interviews. The interview data was analysed using thematic analysis, and the empirical findings were contrasted to the theoretical background. The empirical findings are largely in line with prior literature. Theories about change management and organisational change were found to be applicable to the implementation of electronic invoicing in organisations. The results suggest that not all organisations, individuals, and countries are ready for electronic invoicing.

Organisaatiot kehittävät toimintojaan jatkuvasti pysyäkseen kilpailukykyisinä. Digitalisaation myötä yritykset muuttavat liiketoimintaa digitaalisempaan suuntaan ja etsivät entistä tehokkaampia toimintatapoja. Verkkolaskutus on yksi keino laskutusprosessien tehostamiseen. Verkkolaskutus on tunnettu laskutusmuotona jo vuosikymmenten ajan, mutta se ei ole saavuttanut odotettua suosiota laskutusmenetelmänä. Tämän tutkimuksen tarkoituksena on arvioida tekijöitä, jotka vaikuttavat verkkolaskutuksen käyttöönottoon eurooppalaisissa yrityksissä, ja selvittää, mikä rooli muutosjohtamisella on verkkolaskutuksen käyttöönottoprosessissa. Tutkimus tehtiin toimeksiantona yritykselle X. Yhtiö on parhaillaan kehittämässä uutta laskutusjärjestelmää, jonka tarkoituksena on edistää digitaalisuutta ja automaatiota. Tietojärjestelmän kehittämiseen tarvitaan tietoa verkkolaskutuksen käyttöönoton mahdollisuuksista ja rajoituksista Euroopassa. Tutkimus tehtiin kvalitatiivisena monitapaustutkimuksena. Toimeksiantajayrityksen ja sen tytäryhtiöiden henkilöitä haastateltiin puolistrukturoiduissa haastatteluissa. Haastatteluaineisto analysoitiin temaattisella analyysillä ja esiin nousseita teemoja vertailtiin aiempaan kirjallisuuteen. Tutkimuksen tulokset ovat pitkälti linjassa aikaisemman kirjallisuuden kanssa. Muutosjohtamista ja organisaatiomuutosta koskevien teorioiden havaittiin soveltuvan verkkolaskutuksen toteuttamiseen organisaatioissa. Tulokset viittaavat siihen, että kaikki organisaatiot, ihmiset ja valtiot eivät ole valmiita verkkolaskutuksen käyttöönottoon pääasiallisena laskutusmuotona.
Keywords: electronic invoicing, organisational change, change management, resistance to change